"Popular Catholic University of Risaralda its thirty years 1975-2005" (2021)
When writers write, they write to be read. It is different when the protagonists of the story, big or small, write. These are limited to reeling off the events of a moment in life or history, and by telling them on paper, they can only pretend to leave a Testimony. Something like the Americans did when they landed on the moon. They raised their flag. It is true, nobody sees it. But there it is. And that flag is a Testimony. In the Masters Editorial Collection of the UCPR there is also a Testimony in “FOR YOUR HISTORY. ACCOUNT OF SOME EVENTS THAT GIVEN UCPR LIFE. ”, Published in 2004. A Testimony that will serve as a reference.